Organic Chemistry Conceptual Study of Deoxyribonucleic Acid and Ribonucleic Acid - Mwene-Mbeja, Topwe Milongwe (European Journal of Applied Sciences, 2025)
I report herein the chemical behavior of the main reactive entities in the ribonucleic acid and deoxyribonucleic acid synthesis. Indeed, nitrogenous behave as nucleophiles to concede electrons to electrophiles to furnish the corresponding nucleosides. This step is the fundamental one towards the formation of nucleic acids. The following stage is the combination of nucleosides with the appropriate phosphate groups to produce the adequate nucleotides. The connection between nucleotides through phospho-ester bond formation permits to elucidate the ribonucleic acid (RNA) and deoxyribonucleic acids (DNA) synthesis. In other words, reaction sequences need nitrogenous bases, nucleosides as well as nucleotides including the enzyme, which behave as acids, bases, electrophiles or nucleophiles regarding the synthesis of these kinds of nucleic acids. The hydrolysis of these two nucleic acids can be achieved enzymatically or basically to obtain nucleosides as well as nucleotides.